Três Linguagens em “Dois Irmãos”: Um estudo sobre a adaptação de ‘Dois Irmãos’, de Milton Hatoum para a série de Luiz Fernando Carvalho - Antonio, Danilo Teixeira (Universidade Federal de São Carlos, 2025)
This study addresses the adaptation of the novel "Dois Irmãos" (Two Brothers) by Milton Hatoum into the miniseries directed by Luiz Fernando Carvalho and written by Maria Camargo. The analysis focuses on the differences between the novel and the series, particularly in terms of narrative, stylistic, and structural changes. Considering works and concepts from authors related to the referred field—among others, Walter Benjamin, André Bazin, and Irina Rajewsky—as premises and theoretical references, the analysis conducted in this dissertation aims to contribute to this debate, structured around an intermedia method. As a hypothesis, the research seeks to understand the adaptation, looking for common elements and the necessary narrative, visual, and structural differences that different media require. To that end, reflections on "Dois Irmãos" are presented from three perspectives (corresponding to the three chapters of this work), namely: the book by Milton Hatoum; the screenplay by Maria Camargo; and the series by Luiz Fernando Carvalho.
Three languages in “Dois Irmãos”: A study on the adaptation of ‘Dois Irmãos’, by Milton Hatoum for the series by Luiz Fernando Carvalho
Keywords: Cinema; Milton Hatoum; Roteiro; Adaptação; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA